2010
DOI: 10.1089/jmf.2008.0293
|View full text |Cite
|
Sign up to set email alerts
|

Inability of Legumes to Reverse Diabetic-Induced Nephropathy in Rats Despite Improvement in Blood Glucose and Antioxidant Status

Abstract: Diabetes mellitus has assumed epidemic proportions in most parts of the world, including developing countries, with vascular and renal complications being the major causes of death. Evidence is emerging that legumes play a beneficial role in diabetes and its associated complications. In connection with the above, four groups of alloxan-induced diabetic rats were fed on four different legume-based (Vigna unguiculata ssp. dekindtiana var. dekindtiana, V. unguiculata ssp. unguiculata, Sphenostylis stenocarpa, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…This indirect biomarker of oxidative stress has been reported to be consistently high in diabetes. [4] The findings of this study show that A. gangetica juice as much as glibenclamide reversed the hyperglycemia-induced lipid peroxidation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This indirect biomarker of oxidative stress has been reported to be consistently high in diabetes. [4] The findings of this study show that A. gangetica juice as much as glibenclamide reversed the hyperglycemia-induced lipid peroxidation.…”
Section: Discussionmentioning
confidence: 71%
“…[422] In Lee et al .’s[22] study, phytic acid was reported to reverse the diabetic-induced wasting. Hence, phytic acid, which is found in very high concentration in vegetables, may be responsible for the hypoglycemic effect of A. gangetica juice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of diabetes is on the increase globally and in African communities due to the ageing of the population and drastic lifestyle changes accompanying urbanization and westernization (Sobngwi et al, 2001). Also, studies from five West African communities in Nigeria and Ghana have identified genes within populations that create susceptibility to diabetes (Rotimi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it represents a growing burden on health care systems of African countries, most of which already face difficult economic conditions. The disease remains incurable and can only be controlled with drugs; hence, a scrupulous control is needed to help reduce hyperglycaemia and the risk of long-term complications, which are known to be the major causes of morbidity and mortality (Rotimi et al, 2010). Oxidative stress plays a pivotal role in cellular injury from hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%